Mixed-reality-supported communication for professional home care: system, use, barriers and use cases - Schneider, Cornelia; Rameder, Philipp; Kolmann, Philipp; Trukeschitz, Birgit (Frontiers in Computer Science, 2025)
The rising demand for home care services in Europe, driven by an aging population, presents challenges such as staffing shortages and resource limitations. One way to address these challenges is to increase the use of innovative digital solutions. For this reason, the ‘Care about Care’ project developed the digital Remote Care Assist (RCA) system to enable remote on-site support for professional home care, with a Care Expert Center web application for providing and a mixed-reality Remote Support application for Microsoft HoloLens 2 for receiving support. The solution was tested in two test centers located in Austria and Luxembourg. This paper aims to explore both the general perception and the actual interaction with the RCA system by nursing and care staff and experts in the two test centers. It also aims to identify barriers and potential use cases for successful implementation. We applied a mixed-methods approach by combining usage data measurement and focus group interviews. The results highlight the potential of RCA to improve remote consultations, with key benefits in wound care/medical issues, hands-free interaction and smooth service handovers to colleagues. Barriers were related to the device weight, handling and issues when using the device in areas with poor internet connectivity. The lack of availability of experienced staff to work in the Expert Center has affected usage. Improved device design, centralized expertise and enhanced connectivity are essential for successful integration of RCA into home care.